Resource Use and Conservation of Kabartal Wetland Ecosystem, Bihar - Rai, S.C.; Kumar, Mukesh (National Geographical Journal of India, 2022)
Wetlands are one of the most productive systems and play a significant role in the ecological balance. Kabartal is ecologically most important wetland and considered as one of the largest fresh water oxbow lake in the country. The lake is very rich in biodiversity and was declared protected area in 1986 and as a bird sanctuary in 1989. The purpose of this study is to analys the resource base and major problems of the largest fresh water lake of Bihar. A total of 160 respondents from all sample villages have been covered to collect information on income, fishery, agricultural practices, firewood and fodder requirement. Land and water constitute the major resource of the area. The major positive changes were recorded in built-up area and vegetative cover, whereas, water bodies, swampy land and agricultural land recorded decreasing trend. The total inflow of water in the lake was estimated at 4250 cusecs and outflow about 2769 cusecs. Water quality index value oscillates around 58. It clearly reflects that the water quality of lake is gradually deteriorating because of discharge of domestic waste from surrounding villages, consumptive and non-consumptive use of lake, excessive use of chemical fertilizers and pesticides in the agriculture field. To conserve the lake, it is necessary to initiate proper awareness and education programme in the lake catchment area.